Workplace Fatigue Within Summer Camp: Perspectives From Camp Health Care Providers and Directors. (March 2020) - Dubin, Alexsandra; Garst, Barry A.; Gaslin, Tracey; Schultz, Beth E.
Background: Summer camps engage millions of youth in enrichment opportunities during the summertime while employing a substantial young adult workforce to provide high-quality programs and services to camp participants. Workplace fatigue has been implicated in camp-related injury and illness events, yet few studies have targeted fatigue among camp employees.Purpose: This study aimed to better understand how fatigue impacted employee performance as well as strategies for reducing the negative impacts of fatigue within camp settings.Methodology/Approach: Focus groups were conducted with camp health care providers and directors, and their responses were analyzed using directed content analysis. The analysis process was guided by sensitizing concepts from the literature.Findings/Conclusions: Emergent themes suggested that camp-related fatigue is conceptualized as a construct of time, types, and causes; is a distinct experience leading to setting-specific outcomes; is managed using administrative and peer supports; and is sometimes perceived in positive ways.Implications: This exploratory study highlighted the unique challenges associated with working in a camp setting and the potential development of fatigue as a starting point informing future research. It suggests that future research should include a broader study population, including frontline staff, as well as possible quantitative measures.